Compostagem da casca da mandioca: estudo de caso em uma comunidade no município de Abaetetuba-PA - GARCIA, Waldilene do Carmo (Brazilian Journals Publicações de Periódicos e Editora Ltda, 2020)
The production of fertilizer through composting is an effective way to reduce the expense that the small producer has to grow agricultural products, however, the quality of this compost is an essential advantage for the production to have good quality, the environmental issue is also an issue. Strong reason to reuse organic waste and thus help in the ecosystem balance of nature. From that, one of the reasons for developing this research is the need that family farmers have to buy fertilizer monthly, which ends up compromising the economic profitability of some producers, however, the main objective of this work was to produce fertilizer and raise awareness. To properly dispose of organic waste. The research was based on the community of Camurituba-Beira in the municipality of Abaetetuba-Pá, where eight farmers participated, through official theory and practice in the production of fertilizer, with the socioeconomic survey as an instrument of data collection. The results obtained were 90 kg of fertilizer being tested in some crops to check the quality, in addition, the survey showed that the production of fertilizer by farmers can reduce the expenses with the purchase of this compost. Therefore, the research had socio-environmental relevance, since it worked to raise awareness of the correct disposal of waste, as well as pointing out a possible solution for reducing the purchase of fertilizer.